PENGARUH PENAMBAHAN LIMBAH BOTOL PLASTIK TERHADAP KARAKTERISTIK MARSHALL PADA BETON ASPAL LAPIS PENGIKAT - Puspitasari, Tasia Rizky; Wibisono, Gunawan; Malik, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Plastics have been used for many consumer goods. Polyethylene Terephthalate (PET) is commonly used as non-reusable water bottles. Although the plastic can be recycled and has economic values, the unhandled waste still threatens the environment. PET based waste products have been used as pavement materials in limited applications. This research attempts to investigate the effect of PET waste addition on binder course asphalt concrete (AC-BC) mixtures. The proportion of PET waste added into bitumen was 0, 2, 4, and 6% of bitumen content. Bina Marga 2010 Specification was used to obtain optimum asphalt content and to measure all Marshall characteristic of all samples tested. The results show that the addition of PET waste increased the stability and flow values of mixtures. The optimum PET waste content that still meets the specification was 4% of bitumen content.Keywords : plastic waste, marshall characteristic, AC-BC.